White Arctic vs. Blue Arctic: A case study of diverging stakeholder responses to environmental change. Issue 8 (3rd August 2016) - Newton, Robert; Pfirman, Stephanie; Schlosser, Peter; Tremblay, Bruno; Murray, Maribeth; Pomerance, Rafe
Abstract: Recent trends and climate models suggest that the Arctic summer sea ice cover is likely to be lost before climate interventions can stabilize it. There are environmental, socioeconomic, and sociocultural arguments for, but also against, restoring and sustaining current conditions. Even if global warming can be reversed, some people will experience ice‐free summers before perennial sea ice begins to return. We ask: How will future generations feel about bringing sea ice back where they have not experienced it before? How will conflicted interests in ice‐covered vs. ice‐free conditions be resolved? What role will science play in these debates? Key Points: The Arctic is likely to experience ice‐free summers for decades before warming can be reversed through mitigation or engineering solutions Diverse, often conflicting interests will emerge as ecological conditions, economies, and societies adapt to the new climate Development of options for adaptation or a return to perennial sea ice must account for these stakeholder conflicts